AN INVESTIGATION OF THE EMPATHY LEVELS OF TEAM ATHLETES DURING THE COMPETITION IN TERMS OF CERTAIN VARIABLES - Musa, Mihriay; Bayansalduz, Mehmet; Kepoglu, Abdurrahman; Yanar, Senol; Sunal, Yener (Acta Scientiae et Intellectus, 2024)
The aim of the study is to investigate the empathy levels of team athletes during the competition in terms of some variables. In the study, the “empathy in sports environment” scale developed by Erkus and Yakupoglu (2011) was used to determine the empathy levels of team athletes during the competition. The universe of the research consists of the athletes attending the Faculty of Sport Sciences of Usak University in the 2020-21 academic year. The sample, on the other hand, consisted of 243 team athletes. In the study, it was determined that the empathy levels of the team athletes were at a good level. Again, according to various variables, a difference was found between general empathy, cognitive empathy, and emotional empathy levels. For the trainers to communicate more effectively with their athletes, it has been suggested to use creative drama techniques in their in-service training that they will participate with their athletes.